The Berenstain bears out west - Berenstain, Stan (New York : Scholastic, 2006)
The Bear family is flying over rivers and mountains to get to Uncle Tex's ranch. There is so much to see! Uncle Tex and Aunt Min have plenty of ways to share the fun of the West with the Bear family.